Inducible Prophage Mutant of Escherichia coli Can Lyse New Host and the Key Sites of Receptor Recognition Identification - Chen, Mianmian; Zhang, Lei; Xin, Sipei; Yao, Huochun; Lu, Chengping; Zhang, Wei (Frontiers in Microbiology, 2017)
The use of bacteriophages as therapeutic agents is hindered by their narrow and specific host range, and by a lack of the knowledge concerning the molecular mechanism of receptor recognition. Two P2-like coliphages, named P88 and pro147, were induced from Escherichia coli strains K88 and DE147, respectively. A comparison of the genomes of these two and other P2-like coliphages obtained from GenBank showed that the tail fiber protein genes, which are the key genes for receptor recognition in other myoviridae phages, showed more diversity than the conserved lysin, replicase, and terminase genes. Firstly, replacing hypervariable region 2 (HR2: amino acids 716–746) of the tail fiber protein of P88 with that of pro147 changed the host range of P88. Then, replacing six amino acids in HR2 with the corresponding residues from pro147 altered the host range only in these mutants with changes at position 730 (leucine) and 744 (glutamic acid). Thus we predicted that these amino acids are vital to establish the host range of P88. This study provided a vector of lysogenic bacteria that could be used to change or expand the phage host range of P88. These results illustrated that, in P2-like phage P88, the tail fiber protein determined the receptor recognition. Amino acids 716–746 and the amino acids at positions 730 and 744 were important for receptor recognition.